Optimization of the Preparation Conditions of Borneol-Modified Ginkgolide Liposomes by Response Surface Methodology and Study of Their Blood Brain Barrier Permeability - Zhiyang Lv; Yuwei Yang; Jie Wang; Jing Chen; Junsong Li; Liuqing Di (Molecules, 2018)
Ginkgolides (GG), containing ginkgolide A (GA), ginkgolide B (GB) and ginkgolide C (GC), are mainly prescribed for ischemic stroke and cerebral infarction. However, the ginkgolides can hardly pass the blood-brain barrier (BBB) into the brain. The purpose of this study was to prepare borneol-modified ginkgolides liposomes (GGB-LPs) to study whether borneol could enhance the transport of ginkgolides across the BBB. The preparation conditions of GGB-LPs were optimized by a response surface-central composite design. Also, pharmacokinetics and biodistribution studies of GGB-LPs were conducted using UPLC-MS. The optimal preparation conditions for GGB-LP were as follows: ratio of lipid to drug (w/w) was 9:1, ratio of phospholipid to cholesterol (w/w) was 7:1, and hydrate volume was 17.5 mL. Under these conditions, the GGB-LP yield was 89.73 ± 3.45%. With GGB-LPs, borneol significantly promoted the transport of ginkgolide across the BBB. The pharmacokinetic parameters of GGB-LP were significantly improved too, with Tmax of 15 min and a high drug concentration of 3.39 μg/g in brain. Additionally, the drug targeting index and relative uptake rate of GGB-LP was increased. Borneol-modified ginkgolide liposomes can thus potentially be used to improve the BBB permeability of gingkolide formulations.